The relationship between NFKB, HER2, ER expression and anthracycline -based neoadjuvan chemotherapy response in local advanced stadium breast cancer: A cohort study in Eastern Indonesia. (March 2021) - Indra; Manginstar, Christian; Islam, Andi Asadul; Sampepajung, Daniel; Hamdani, William; Bukhari, Agussalim; Syamsu, Salman Ardy; Prihantono; Smaradania, Nilam; Faruk, Muhammad
Abstract: Introduction: Neoadjuvant chemotherapy has become the standard form of treatment for locally advanced breast cancer. Chemoresistence is a problem that limits the effectiveness of chemotherapy. Therefore, predictive biomarkers are needed to choose the appropriate chemotherapy to the right patient. The role of NF-кb expression as a predictive biomarker of neoadjuvant chemotherapy response needs to be investigated in patients with locally advanced breast cancer who are treated with a regimen of cyclophosphamide-doxorubicin-5FU (CAF). Methods: This observational study used the prospective cohort method to examine 62 samples. CAF was administered at 3-week intervals for 3 cycles of chemotherapy. The data utilized in this study include the positive and negative expression of NF-κB, ER, and HER2 overexpression. The cases were divided into groups that were responsive and non-responsive to the neoadjuvant chemotherapy. Results: The average age in the youngest group was 26 years, and that in the oldest was 66 years. The highest age group was subjects in their 50s, which had 26 cases (41.9%). The majority of the cases were moderate grade with 38 cases (61.3%). The percentage of responsive subjects was higher in the groups with negative NF-κB expression (82.5%), positive HER2 status (85.7%), and negative ER status (71.9%). It was found that 37 cases (59.7%) were responsive to CAF, while 25 cases (40.3%) were non-responsive. There was a significant relationship between NF-κB expression and chemotherapy response (p < 0.05), and the percentage of responsive subjects was higher among those with negative NF-κB expression (82.5%) than positive NF-κB expression (18.2%). Conclusion: NF-κB expression, ER status, and HER2 have a significant relationship with the response to anthracycline-based neoadjuvant chemotherapy for local advanced breast cancer, and NF-κB expression has the most significant relationship with the chemotherapy response. Therefore, NF-κB expression should be considered as a predictive biomarker for the response to CAF regimens. Highlights: Neoadjuvant chemotherapy is standard treatment for local advanced breast cancer. Cyclophosphamide-doxorubicin-5FU (CAF) regimens are widely used in neoadjuvant chemotherapy. NF-κB expression, ER status, HER2, and the CAF response are significantly related. Cases with negative NF-κB expression were 10 times more likely to respond to CAF. NF-κB expression should be considered as a predictive biomarker.